Kompetensi Profesional Guru Bahasa Arab dan Masalah Pembelajaran Bahasa Arab - Manoppo, Ningsih; Arif, Muh (Assuthur: Jurnal Pendidikan Bahasa Arab, 2023)
This article aims to explain the professional competence of teachers and the problems encountered in learning Arabic. The research method used is literature review. In fact, the teacher is a strategic profession, the teacher has a noble duty to educate and build the character of the nation. Therefore, teachers must know and develop their competence, especially in teaching Arabic. The competencies in question are linguistic and non-linguistic competencies. The fact is that in the field there are still many Arabic teachers who do not meet the ideal criteria, so it is necessary to hold self-development training in order to become a professional Arabic teacher.